Advanced computational modelling of metal organic frameworks and their performance - Cooley, Isabel (2023)
The performance of metal organic frameworks (MOFs) in applications relevant to modern technological challenges is assessed using selected computational modelling methods. This class of materials has gained significant attention in recent years thanks to its ability to display advanced properties, including high surface area and tunability. This work discusses MOFs and the computational techniques which may be used to obtain useful information about them in the context of modern advanced materials and methods.